Naturally occurring canine osteosarcoma in the dog animal model for research of targeted radiotherapy using beta-emitting radioisotopes with various ligands - Dormehl, I.C. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2013.